Heart Care By Diet Mobile Application - Kharuddin, Amirul Asyraf (Universiti Teknologi PETRONAS, 2021)
Many people from all backgrounds are at risk of having a heart attack, especially old people. Even young people also may get a risk of having a heart attack. A heart attack can be defined as an acute episode of coronary heart disease characterized by the death or damage of heart muscle as a result of insufficient blood supply to the heart. An unhealthy diet is one of the major factors that may contribute to death caused by a heart attack as experts believe that eating foods high in cholesterol would lead to more heart disease. This is because a high amount of cholesterol would make it harder for blood to get through to other parts of the body. Hence, a blockage is developed inside people’s arteries which are made up of fat and cholesterol. As for the perspective of the people who concern with their heart health, they need to monitor their daily cholesterol intake based on a daily diet.